21st‐century transnational real estate development: What, where, who, how and why?. Issue 5 (13th April 2021) - Koelemaij, Jorn; Derudder, Ben
Abstract: In this paper, we review the emerging geographical literature dealing with large‐scale transnational real estate development projects (TREDs). Predominantly geared towards (often imagined) upper middle classes through eye‐catching and mixed‐use projects, the distinctive feature of TREDs is that they are facilitated by a formative transnational investor/developer. Based on a literature review and an analysis of fDi Markets data, we discuss the nature of TREDs, where they can be found, which actors and companies are mainly responsible for them, how they emerge and materialize (or not), and why they are so relevant in contemporary economic geography. It is argued that TREDs are both characteristic of and contribute to the rise of authoritarian urban development practices. We furthermore show that both fictitious and symbolic capital play a role and that real estate and geopolitical strategies are inextricably linked with one another. Given that interscalar dynamics between the main facilitators of TREDs are still relatively understudied within economic geography, we end with a call to develop more in‐depth perspectives on these matters.